Role of 5-HT2 receptors family in the allergy-induced increased aorta contractile responses to 5-HT - Campos-Bedolla, P; Torrejón-González, E G; Mendoza-Mejía, D; Vargas, M H; Segura-Medin, P; Carbajal, V; Rodríguez-Márquez, A; Martínez-Silva, A V (Physiological research, 2023)
Asthma poses an increased risk for cardiovascular disorders, suggesting that allergy, which is an underlying process in asthma, causes atypical functioning of organs other than lungs. In a previous study in a guinea pig asthma model, we concluded that allergic sensitization increased aorta contractile responses to 5-HT. To further characterize these responses, here we explored the role of the 5-HT2 receptors family. We found that TCB-2 (5-HT2A agonist) and WAY161503 (5-HT2C agonist) induced aorta contractions resembling those elicited by 5-HT but less intense (~43 % and ~25 %, respectively). In these experiments, aortas from sensitized guinea pigs showed increased contractions to TCB-2, but not to WAY161503. In turn, MDL 100907 (5-HT2A antagonist) and RS-102221 (5-HT2C antagonist) caused a notably and a mild reduction of the 5-HT-induced contractions, respectively, with no differences seen between sensitized and non-sensitized tissues. BW723C86 (5-HT2B agonist) did not induce contractile responses and RS-127445 (5-HT2B antagonist) did not modify the contractile responses to 5-HT. In non-sensitized aortas, the pattern of protein expression of receptors was 5HT2B>5-HT2A=5-HT2C, which did not change in sensitized animals. In conclusion, we found that allergic sensitization increased the aorta contractile responses to 5-HT, partly mediated by enhanced responses of 5-HT2A receptors, which was unrelated to changes in the expression of these receptors.
Keywords: morčata; Animals; Receptors, Serotonin; Guinea Pigs; aorta; serotonin; Receptors, Serotonin, 5-HT2; zvířata; Aorta; receptory serotoninové 5-HT2; bronchiální astma; receptory serotoninové; Asthma; Serotonin